2018
DOI: 10.1016/j.jclinepi.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review highlights the need to investigate the content validity of patient-reported outcome measures for physical functioning in patients with low back pain

Abstract: The content validity of PROMs to measure physical functioning in patients with LBP is understudied. Structural validity of several widely used PROMs is problematic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 145 publications
(83 reference statements)
0
73
0
1
Order By: Relevance
“…That is, the field has largely been driven by assumptions that the GROC is a ‘gold standard’ for evaluating true change in a respondent’s condition or status, and that all items on the comparator PROM are of equal importance to all people with that condition. The work presented herein challenges the valorisation of the GROC as a gold standard for change, and prior work has challenged the notions that all PROM items are equally important 9 41 42. It is therefore possible that the very constructs being evaluated require greater critical discourse before authors can say, with confidence, that one scale functions well or poorly based on its associations with another scale.…”
Section: Discussionmentioning
confidence: 94%
“…That is, the field has largely been driven by assumptions that the GROC is a ‘gold standard’ for evaluating true change in a respondent’s condition or status, and that all items on the comparator PROM are of equal importance to all people with that condition. The work presented herein challenges the valorisation of the GROC as a gold standard for change, and prior work has challenged the notions that all PROM items are equally important 9 41 42. It is therefore possible that the very constructs being evaluated require greater critical discourse before authors can say, with confidence, that one scale functions well or poorly based on its associations with another scale.…”
Section: Discussionmentioning
confidence: 94%
“…The systematic review on physical functioning PROMs revealed low or very low quality evidence underpinning the content validity of all the PROMs, with the exception of the 24-item RMDQ (RMDQ-24), which displayed high quality evidence of insufficient comprehensiveness and sufficient comprehensibility. 18 High quality evidence of insufficient unidimensionality was found for ODI 1.0, RMDQ-24, and RMDQ-18; unidimensionality of other PROMs was underpinned by moderate quality evidence, or no studies were found (Appendix 2, available online as supplemental digital content at http://links.lww.com/PAIN/A511 ). 18 The systematic review on pain intensity PROMs highlighted that content validity of visual analogue scale (VAS), Numeric Rating Scale (NRS), and pain severity subscale of the Brief Pain Inventory (BPI-PS) was underpinned by (very) low quality evidence (Appendix 2, available online as supplemental digital content at http://links.lww.com/PAIN/A511 ) (Chiarotto et al, 2018.…”
Section: Resultsmentioning
confidence: 99%
“… 18 High quality evidence of insufficient unidimensionality was found for ODI 1.0, RMDQ-24, and RMDQ-18; unidimensionality of other PROMs was underpinned by moderate quality evidence, or no studies were found (Appendix 2, available online as supplemental digital content at http://links.lww.com/PAIN/A511 ). 18 The systematic review on pain intensity PROMs highlighted that content validity of visual analogue scale (VAS), Numeric Rating Scale (NRS), and pain severity subscale of the Brief Pain Inventory (BPI-PS) was underpinned by (very) low quality evidence (Appendix 2, available online as supplemental digital content at http://links.lww.com/PAIN/A511 ) (Chiarotto et al, 2018. Measurement properties of Numeric Rating Scale, Visual Analogue Scale and Pain Severity subscale of Brief Pain Inventory in patients with low back pain: a systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…PRO instruments have been utilized to identify and measure LBP-specific outcomes (Longo, Loppini, Denaro, Maffulli, & Denaro, 2010). However, the most widely used LBP-specific PRO instruments do not cover the biopsychosocial perspective (Ibsen, Schiottz-Christensen, Melchiorsen, Nielsen, & Maribo, 2016), and challenges concerning content validity have been reported (Chiarotto, Ostelo, Boers, & Terwee, 2018). Thus, there is a need to explore patients' perspectives on the development and application of a LBP-specific PRO instrument.…”
mentioning
confidence: 99%